TEORI TZVETAN TODOROV UNTUKMEMBEDAH UNSUR NARATIF DALAM FILM SEJUTA SAYANG UNTUKNYA DAN RELEVANSINYA DENGAN PEMBELAJARAN TEKS NARASI DI SMP - Dita Prisilia Lestari; Dindin M.Z.M; Setiawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to analyze a film using Tzvetan Todorov's theory which is then used for teaching narrative texts in junior high schools. Film is one of the creations of humans that contains entertainment, education, about messages, about life and films can be a powerful tool to educate and indoctrinate the audience. This study examines a narrative element analysis film, especially the film Sejuta Sayang Untuknya. This film depicts a father who lives alone with his daughter. This study aims to analyze the narrative elements contained in the film. Narrative In this film contains a message that a father who fights for his daughter so that all her wishes come true. The method used is a qualitative methodology using Tzvetan Todorov's narrative analysis. The technique of collecting data from this study is in the form of observation and documentation. The results of this study show the initial groove, middle groove and final plot. The conclusion of this study is that the film Sejuta Sayang Untuknya is a film with a family theme full of education, depicting the very important role of the father in the family.